Model for Increasing Organizational Performance through Affective Commitment and Innovation Behavior in Batik MSMEs in Pati Regency - Agustiya Fatriya Rizky (Perspective Humanities and Social Sciences, 2025)
This research proposal is put forward in order to identify how the influence of the role of Innovation Behavior has on Organizational Performance, the influence of Innovation Behavior on Affective Commitment. Influence of Affective Commitment on Organizational. performance. The type of research that will be carried out is explanatory research, where this research aims to analyze the relationship between exogenous variables and endogenous variables. Variables in this research include Organizational Performance, Innovative Behavior, Affective Commitment. The population to be analyzed in this research proposal is the population in this study. In this study, the population taken was batik UMKM from Pati Regency, with a total population of 333 people from batik UMKM in Pati Regency. The sample in this study was determined using a purposive sampling method with a total of 100 respondents. This research uses quantitative methods with primary data obtained from questionnaires. Sample selection will use a non-probability sampling method, namely a sampling technique where not all of the population can be sampled. Data analysis uses the Partial Least Square (PLS) method with SmartPLS. The research results show that affective commitment has a positive and significant influence on organizational performance. Affective commitment has a positive and significant influence on innovation behavior. Innovation behavior has a positive and significant influence on organizational performance.